Methodological issues in the epidemoiology of risk assessment and mortality - Brant, L. J. (Array, 1990)
Risk factor analyses are widely used in epidemiological studies of morbidity and mortality. This paper discusses different models that are used for such studies and addresses numerous issues that arise in the subsequent analyses. Methodological issues are illustrated by examining the relationship between relative body weight and mortality in a cohort of males participating in a longitudinal study of normal aging